FAKTOR - FAKTOR YANG MEMPENGARUHI PERAN PEREMPUAN DALAM MENINGKATKAN PENGHASILAN RUMAH TANGGA MELALUI SEKTOR FORMAL DAN INFORMAL - Dewi Mulyasari Ahtobara; Holilulloh Holilullah; Muhamad Mona Adha (FKIP Unila, 2012)
This research focused on the problems of factors which contribute to women’ role in improving household income through formal and informal sector in Purworejo Village, Pesawaran Regency. This research was descriptive research. The data was collected though inquiry/poll and documentation. There were 35 women (housewives) of Purworejo Village participated in this research. The validity and reliability of the poll were measured with Pearman Brown Formula. Then the data was analyzed with Chi Square Formula. The result showed that there was significant difference of percentage of factors which contribute to women’ Keywords: role of women, autonomy,formal and informal sector